United Kingdom Frozen Shoulder Trial (UK FROST), multi-centre, randomised, 12 month, parallel group, superiority study to compare the clinical and cost-effectiveness of Early Structured Physiotherapy versus manipulation under anaesthesia versus arthroscopic capsular release for patients referred to secondary care with a primary frozen shoulder: study protocol for a randomised controlled trial - Stephen Brealey; Alison L. Armstrong; Andrew Brooksbank; Andrew Jonathan Carr; Charalambos P. Charalambous; Cushla Cooper; Belen Corbacho; Joseph Dias; Iona Donnelly; Lorna Goodchild; Catherine Hewitt; Ada Keding; et al. (Trials, 2017)
Abstract Background Frozen shoulder (also known as adhesive capsulitis) occurs when the capsule, or the soft tissue envelope around the ball and socket shoulder joint, becomes scarred and contracted, making the shoulder tight, painful and stiff. It affects around 1 in 12 men and 1 in 10 women of working age. Although this condition can settle with time (typically taking 1 to 3 years), for some people it causes severe symptoms and needs referral to hospital. Our aim is to evaluate the clinical and cost-effectiveness of two invasive and costly surgical interventions that are commonly used in secondary care in the National Health Service (NHS) compared with a non-surgical comparator of Early Structured Physiotherapy. Methods We will conduct a randomised controlled trial (RCT) of 500 adult patients with a clinical diagnosis of frozen shoulder, and who have radiographs that exclude other pathology. Early Structured Physiotherapy with an intra-articular steroid injection will be compared with manipulation under anaesthesia with a steroid injection or arthroscopic (keyhole) capsular release followed by manipulation. Both surgical interventions will be followed with a programme of post-procedural physiotherapy. These treatments will be undertaken in NHS hospitals across the United Kingdom. The primary outcome and endpoint will be the Oxford Shoulder Score (a patient self-reported assessment of shoulder function) at 12 months. This will also be measured at baseline, 3 and 6 months after randomisation; and on the day that treatment starts and 6 months later. Secondary outcomes include the Disabilities of Arm Shoulder and Hand (QuickDASH) score, the EQ-5D-5 L score, pain, extent of recovery and complications. We will explore the acceptability of the different treatments to patients and health care professionals using qualitative methods. Discussion The three treatments being compared are the most frequently used in secondary care in the NHS, but there is uncertainty about which one works best and at what cost. UK FROST is a rigorously designed and adequately powered study to inform clinical decisions for the treatment of this common condition in adults. Trial registration International Standard Randomised Controlled Trial Register, ID: ISRCTN48804508 . Registered on 25 July 2014.